Emergency medicine secrets - Bakes, Katherine M.; Buchanan, Jennie A.; Moreira, Maria; Byyny, Richard; Pons, Peter T. (Secrets, 2022)
Emergency Medicine Secrets, 7th Edition, offers practical, up-to-date coverage of the full range of essential topics in this dynamic field. This highly regarded resource features the Secrets' popular question-and-answer format that also includes lists, tables, pearls, memory aids, and an easy-to-read style - making inquiry, reference, and review quick, easy, and enjoyable.